KNOWLEDGE AND AWARENESS LEVEL ABOUT ROTATOR CUFF TEARS AMONG SAUDI POPULATION (CAHIERS MAGELLANES-NS, 2024)
One of the most prevalent shoulder disorders, tendinopathy, partial or complete rotator cuff or biceps tendon complex tears, bursitis, or labral lesions are some of the ways that rotator cuff-related discomfort can appear. Despite the symptoms, rotator cuff illness affects persons of all ages, with incidence rates 10% higher in those under the age of 20 and 62% higher in those over the age of 80. Recent genetic research suggests that hereditary variables may influence the occurrence of rotator cuff issues. In the Western world, rotator cuff repairs have significantly increased during the last 15 years.Objective: This study's main objective was to assess the Saudi population's level of knowledge and awareness regarding rotator cuff tears.Methods: A comprehensive cross-sectional study involving 371 participants is set to be conducted in Saudi Arabia between 2023 and 2024. The data will be gathered using a simple English and Arabic questionnaire, which includes questions about rotator cuff tears and the prevalence of relevant knowledge among Saudi Arabians regarding causes, signs, symptoms, detection methods, management procedures, and complications associated with rotator cuff tears. Once the data collection phase is complete, the gathered data will be entered into Microsoft Excel software. Subsequently, this data will be imported into the SPSS application, where it will be subjected to statistical analysis.Results: the total sample size was 371 individuals. Regarding knowledge and awareness score of rotator cuff tears among Saudi population, there were 19.7% of participants demonstrated a good level of knowledge on rotator cuff tears, while 29.6% exhibited a moderate level of knowledge. A significant proportion, 50.7%, showed a low level of knowledge. As regard the relation between knowledge level of rotator cuff tears and sociodemographic characteristics, there was a statistically significant relation to the occupation (p value = 0.008) and whether the participants were diagnosed with rotator cuff injury before (p value = 0.010). It also shows statistically insignificant relation to gender, age, nationality, education level, monthly income, lifestyle, and the dominant hand of the participants. Conclusion: the study revealed a concerning lack of knowledge and awareness about rotator cuff tears among the Saudi population, with only a small percentage demonstrating a good level of knowledge on the condition. This lack of awareness is consistent with findings from previous studies in Saudi Arabia, Kuwait, and the United States, indicating a global issue of insufficient understanding about rotator cuff tears.